2014
DOI: 10.3390/membranes4030630
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin: Roles in Cell-Surface Protein Expression

Abstract: In order to perform their designated functions, proteins require precise subcellular localizations. For cell-surface proteins, such as receptors and channels, they are able to transduce signals only when properly targeted to the cell membrane. Calreticulin is a multi-functional chaperone protein involved in protein folding, maturation, and trafficking. However, evidence has been accumulating that calreticulin can also negatively regulate the surface expression of certain receptors and channels. In these instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…As a chaperone protein, calreticulin is also linked with HSP90. This protein is expressed on the cellular surface and its putative role in cell adhesion, migration or apoptosis has been documented 49 . In addition, calreticulin modulates integrin-dependent Ca 2+ signaling [Michalak et al, 1999] and different patterns of expression have been reported during implantation in mice [Cheng et al, 2009].…”
Section: Structural/cytoskeleton Calcium Metabolism and Membrane Promentioning
confidence: 99%
See 1 more Smart Citation
“…As a chaperone protein, calreticulin is also linked with HSP90. This protein is expressed on the cellular surface and its putative role in cell adhesion, migration or apoptosis has been documented 49 . In addition, calreticulin modulates integrin-dependent Ca 2+ signaling [Michalak et al, 1999] and different patterns of expression have been reported during implantation in mice [Cheng et al, 2009].…”
Section: Structural/cytoskeleton Calcium Metabolism and Membrane Promentioning
confidence: 99%
“…In addition, calreticulin modulates integrin-dependent Ca 2+ signaling [Michalak et al, 1999] and different patterns of expression have been reported during implantation in mice [Cheng et al, 2009]. This protein is expressed on the cellular surface and its putative role in cell adhesion, migration or apoptosis has been documented 49 . In addition, calreticulin modulates integrin-dependent Ca 2+ signaling 50 and different patterns of expression have been reported during implantation in mice 51 .…”
Section: Structural/cytoskeleton Calcium Metabolism and Membrane Promentioning
confidence: 99%
“…Calreticulin (CALR) is an endoplasmic reticulum (ER)-resident protein that regulates the functions of numerous proteins by chaperoning them to their active sites in response to Ca 2+ [1,2]. Structurally and functionally, mature human CALR (residues 18-417; UniProt ID: P27797) can be divided into three domains, a globular N-terminal domain (N-domain, N-CARL, residues 18–197), an extended proline-rich P-domain (residues 198–308), and an acidic C-terminal domain (C-domain, C-CARL, residues 309–417) [3,4].…”
mentioning
confidence: 99%
“…Calreticulin is another protein located in the endoplasmatic reticulum with chaperon properties and both HSPs and calreticulin are DAMPs with pro-inflammatory abilities [58,104]. These molecules may very well be targets of aluminium ions resulting in changed conformation, modified function, and cellular re-localization.…”
Section: Cellular Stress Functionsmentioning
confidence: 99%